SENSITIVITY, PRECISION, AND F1 SCORE OF WEARABLE DEVICES IN ABSENCE SEIZURE MONITORING: A SYSTEMATIC REVIEW - Amri, Zidan Dzulyadain; Setyoadji, Yusuf Omar; Sadinah, Fahrin; Ernanda, Shelby Amrus; Damayanti, Ria (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Absence seizure is one of the most common forms of generalized epilepsy. Wearable devices have been proposed as useful tools to improve clinical care by providing continuous monitoring of patients. This study aimed to evaluate the use of wearable devices for detecting and monitoring absence epilepsy. Methods: This systematic review was performed using PRISMA standards and included cohort studies investigating wearable devices as monitoring tools for absence epilepsy. Literature searches were performed in PubMed, Science Direct, Cochrane, and Google Scholar. Results: Eleven cohort studies published between 2012 and 2025 from France, Turkey, Portugal, Netherlands, Denmark, Belgium, Georgia, USA, and Boston were included, with a total of 1,305 participants. All studies assessed wearable devices for detecting absence seizures and reported diagnostic performance using sensitivity, precision, and F1 score. The pooled descriptive synthesis showed a mean sensitivity of 0.897 (range 0.791–1.000; 11 studies), a mean precision of 0.831 (range 0.540–0.950; 7 studies), and a mean F1 score of 0.858 (range 0.740–0.9639; 7 studies). Only descriptive analysis was possible as most studies did not provide raw diagnostic data or confidence intervals. Conclusion: Wearable devices demonstrate promising performance in detecting absence seizures among patients with absence epilepsy, with high sensitivity, acceptable precision, and overall robust F1 scores across the included studies. However, the lack of standardized data reporting and confidence intervals limits the possibility of meta-analysis. Further large-scale prospective studies are required to validate these findings and support clinical implementation.